THE DEVELOPMENT OF PHYSICAL EDUCATION TEACHER PROFESSIONAL STANDARDS COMPETENCY (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2012)
This study aims to determine the needs develops and delivers specific professional standards competency, and validation of a specific professional standards competency for physical education, health and sport teachers. The method research and development design (R&D). The study did in Palu City and performed in three phases is: a preliminary study; development stage, and; validation. Preliminary studies stage is using a qualitative approach. The development stage is the formulated of the draft standards of professional competence for Physical Education, Health and Sport teachers. Further stage is evaluated in the expert forum (FGD) and validator. Sources of data in this study were teachers of physical education, health and sport, headmaster and Department of education in Palu. Data were collected by interview (questionnaire) and documentation. Analysis data used of Interaction Model of Miles and Huberman (1992) is collect data, reduce data, compile the results of data reduction, and; data verification. The results of this study are: 1) needed for a specific professional competency standards for physical education, health and sport teachers, this show from whole percentage that 89,98 % SMP, SMAN and SMKN teachers in Palu City need specific of professional competency standards for physical education, health and sport teachers 2) development of specific standards professional of competence for physical education, health and sport teachers formulated in six dimensions are capability of physical education, health and sport science; understanding of curriculum development in physical education, and health; learning of physical education, and health; assessment and evaluation in physical education, health and sport, and the professional responsibility of physical education health and sport teachers, 3) the validation performed by the nine validator that agreed of standards professional competence that is specific to physical education, health and sport teachers for use. The conclusion are: 1) The existence of a specific professional competency standards for physical education, health and sport teachers is needful, 2) standards of professional competence which contains the criteria developed specifically for Physical education, health and sport teachers, 3) the validator states that the standard of professional competence has been able to apply to physical education, health and sport teacher. Suggestions in this study include: 1) physical education, health and sport teachers should be experts in physical education,health and sport 2) institution that held a coaching and training for physical education, health and sport teachers refer to these standards of professional competence, and, 3) College provide courses according to standards of professional competence physical education, health and sport teachers agreed.